Qudwatuna as a Leadership Model in Education Quality Development - Romlah, Siti; Hamzah, Akhmad Fauzi; Makhzuniyah, Minhah (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines the implementation of educational quality management at MA Dalwa, which is located in the Darullughah Wadda'wah Raci Bangil Islamic Boarding School. Using a qualitative approach and case study design, this study explores the application of the